Analyzing the function of metaverse technology in the retention and absorption of knowledge using the integrated approach of interpretive structural modeling and structural equations - Seyed Mojtaba Hosseinibamakan; Hajar Soleymanizadeh; Mehran Ziaeian (مدیریت راهبردی دانش سازمانی)
Considering the importance of knowledge management in improving the performance of various industries, including the electricity industry, in areas such as reducing safety risks, using complex systems, etc., it is necessary to maintain and absorb knowledge in order to improve the skill level of employees. The purpose of this research is to investigate how Metaverse technology works in retention and absorbing knowledge in the electricity industry of the country. In order to carry out the present research, at first, 12 achievements resulting from the operation of Metaverse technology were identified by reviewing the background of the research and were approved by the experts and managers of the country's electricity industry. In the following, by using judgmental sampling method and asking opinions from 15 academic experts and managers of the country's electricity industry, the relationship between the achievements of Metaverse technology in the country's electricity industry was identified and a conceptual model of how Metaverse technology works in retention and absorbing knowledge. It was presented in the electricity industry of the country. In order to fit the presented model, structural equation modeling approach and Smart PLS software were used. Interpretive structural modeling has shortcomings such as relying on the intuition and judgment of the participants. This problem affects the validity of interpretive structural modeling approach. To solve this problem and in order to validate the presented model resulting from the interpretive structural modeling approach, the structural equation modeling approach and Smart PLS software were used. Using available sampling method, 350 questionnaires were distributed among the employees and managers of the country's electricity industry, and 307 questionnaires were returned. The results of this research showed that metaverse technology through capabilities such as environmental artificial intelligence, simulation, natural language processing, use of social networks, data analysis, knowledge organization, cooperation, knowledge sharing. Access to extensive resources, interactive education, knowledge storage and knowledge updating play a fundamental role in retention and absorbing knowledge.